Freedom to Connect: Insight Into the Existential Dimension of Transformative Learning in a Graduate Seminar. (July 2016) - Sohn, Brian K.; Plaas, Kristina; Franklin, Karen; Dellard, Tiffany; Murphy, Brenda; Greenberg, Katherine H.; Greenberg, Neil B.; Pollio, Howard R.; Thomas, Sandra P.
Previous analyses of transformational learning (TL) focused on rational or nonrational processes such as critical reflection on an uncomfortable personal situation or emotional learning. In this phenomenological study, researchers examined existential dimensions of TL. Individual interviews were analyzed to identify the lived experiences of eight participants in a graduate seminar. Participants described their experience to be "different" from other courses and "relevant and applicable" to their lives. They found the "atmosphere" of the course to be "free" from institutional obligations and "open" to ideas. They were "collaborative" in exploring course content and "connected" with other students, "safe" to share perspectives and understandings, and "comfortable" to explore content in their own way. Study findings suggest that discomfort is not necessary for TL to occur when students build relationships and learn in a safe and open classroom climate and that such an environment supported spontaneous application of course content to student lives.